The use of complementary and alternative medicine among surgical patients: a cross-sectional study - Abdelkarim Barqawi; Aia Egbaria; Arwa Omari; Noura Abubaji; Faris Abushamma; Amer A. Koni; Sa’ed H. Zyoud (Perioperative Medicine)
Abstract Background The use of complementary and alternative medicine (CAM) has increased substantially around the world; various global studies have documented the use of CAM by surgical patients in the preoperative period, with rates of herbal medications and other nonherbal treatments ranging from 12 to 69%. This study aimed to identify the prevalence of CAM and its patterns of use among surgical patients. Methods From December 2020 to April 2021, a descriptive cross-sectional study was undertaken in Palestine. A face‒to-face interview questionnaire was used. The participants were asked questions regarding sociodemographics, clinical information, CAM usage, reasons for its use, and opinions on its efficacy. Results Among the 300 surgical patients who were interviewed in this study, 252 (84.0%) reported that they had ever used CAM, while a total of 122 (48.4%) had used CAM before their surgery, 81.7% of the respondents used herbal methods, and 64.7% of them used nonherbal methods. CAM use among our study population was not linked to specific demographics or other characteristics, except health insurance (p = 0.004). The most commonly used herbs among surgical patients are Salvia officinalis L. (Sage) (84.1%) and Pimpinella anisum L. (Anise) (75.5%). The highest percentage was found among patients with university qualifications (73.2%), who used more than three methods (p < 0.001). In addition, 59.4% of the females used more than three therapies, whereas 45.9% of the males did (p = 0.032). Conclusions The herbal methods used are common among surgical patients in Palestine and are consistent with the enormous increase in the use of CAM. Therefore, awareness should be raised among the public regarding the risks and benefits of CAM use.